Take Charge of Your Nursing Career, Second Edition. - Marshall, Lois Sarah. (20211021 Series, 2021)
Take Charge of Your Nursing Career, Second Edition provides nurses with a unique and distinct perspective to develop and manage their careers from beginning to end. With timely and relevant topics, strategies, tips, and examples, author, Lois Sarah Marshall helps nurses define their personal career trajectory no matter what point they are in their journey.